The Behavior of Dredged Soil-Shredded Rubber Embankment Stabilized with Natural Minerals as a Road Foundation Layer - Komang A. Utama; Tri Harianto; A. B. Muhiddin; Ardy Arsyad (Salehan Institute of Higher Education, 2023)
Recently, geotechnical studies have been conducted more progressively to utilize dredged soil. The inclusion of shredded rubber (SR) and natural minerals (NM) to stabilize dredged soil (DS) has become an exciting issue in the geotechnical field. This technique can be a promising environmental innovation for the future. This study aimed to investigate the unconfined compressive strength (UCS), California bearing ratio (CBR), and embankment performance under the strip footing test. The UCS sample was prepared using shredded rubber with a proportion of 2% and 3% and natural minerals with a proportion of 3%, 6%, 9%, and 12% from the dry weight of the soil. Whereas for the CBR samples (both in un-soaked and soaked conditions) were also prepared with a proportion of 2% and 3% shredded rubber and 6% and 9% natural minerals from the dry weight of the soil as well. The strip footing test was conducted in small-scale laboratory tests to evaluate the performance of stabilized dredged soil embankments. The applied load test was gradually increased until the embankment collapsed. The results showed that adding shredded rubber and natural minerals could increase the UCS value by 3–4 times and the CBR value by 2–3 times. Furthermore, 84% and 116% efficient results were obtained in the strip footing test for the 7 and 14 days of curing, respectively. Therefore, the utilization of dredged soil stabilized with SR and NM can be considered for use as a road foundation layer. Doi: 10.28991/CEJ-2023-09-05-016 Full Text: PDF